Exposing the estuarine mysid Mesopodopsis Slabberi to heavy metal lead: an ecotoxicological and experimental approach - Sardo, Ana M. (2012)
In this work, ecotoxicological tests were performed, using the estuarine mysid Mesopodopsis slabberi. After an acclimation period mysids were exposed to different sublethal lead concentrations for 48h. The concentrations tested were 0.005, 0.01, 0.02, 0.04, 0.08, 0.16, 0.32, 0.64, 0.80, 1.00, 1.20 and 1.40 mgL(-1), with seven replicates for each concentration. Mortality and physicochemical parameters were measured. Survival organisms were sacrificed and submitted to histology process. Histological effects were analyzed in several tissues and results are presented and discussed in this work. There were observed lead accumulations in organisms exposed to concentrations in the range of 0.32 to 1.40 mgL(-1), mainly on muscular tissue, gonad and cuticular lens. These results indicate that M. slabberi can be a sensitive indicator of exposure to contamination by lead.